Institutional change and network evolution: explorative and exploitative tie formations of co-inventors during the dot-com bubble in the Research Triangle region. Issue 8 (3rd August 2017) - Menzel, Max-Peter; Feldman, Maryann P.; Broekel, Tom
ABSTRACT: Institutional change and network evolution: explorative and exploitative tie formations of co-inventors during the dot-com bubble in the Research Triangle region. Regional Studies . This paper investigates how institutions impact tie formation, arguing that institutions can direct firm strategies towards exploration or towards exploitation. It translates these strategies into tie formations: explorative tie formation produces structural holes as a source of good ideas, while exploitative tie formation closes structural holes to facilitate the mobilization of resources to move ideas into products. Using the example of co-inventors in information and communication technology in Research Triangle region during the dot-com bubble, explorative tie formation during the bubble and exploitative tie formations after its burst were expected. Stochastic actor-oriented models did not clearly support our assumptions. It was found that the emergence of venture capital led to a large variance in connection patterns during the bubble, probably resulting from overlapping institutional effects. After the burst of the bubble, these incoherencies disappeared.